Importancia, manejo y control de extraíbles e incrustaciones (pitch) en la fabricación de papel - Aguilar Rivera, Noé (Instituto de Ecología, A.C., 2016)
A description of problems related to wood extractives and pitch deposition in the pulp and paper industry is made. Extractives are released during the pulping of wood and bleaching of pulp. In pulping, wood extractives increase consumption of pulping chemicals, impair the color and brightness of unbleached pulp and cause a sticky deposit on pulping and bleaching equipment. The effects of wood resin will often depend on how the process is undertaken. To avoid excessive build-up of wood resin, it may be necessary to minimize the amount of wood resin introduced into the process, It might be helpful to have points of wood resin removal in the process. Some of these options are discussed in detail. This paper explores some issues and proposes ways to avoid and combat wood resin deposition problems.